Sentiment analysis of subcutaneous and intravenous immunoglobulin therapy: public healthcare perception through social media discourse - Tarango-García, Alejandro; Rodríguez-Narciso, Silvia; Castañeda-Leyva, Netzahualcóyotl; Prieto-Nevárez, Hannia M.; Lugo Reyes, Saul O.; Espinosa-Rosales, Francisco J.; Espinosa-Padilla, Sara Elva; Staines-Boone, Aidé T.; Torres-Bernal, Luis F.; Álvarez-Cardona, Aristóteles (Frontiers in Immunology, 2024)
Purpose: Immunoglobulin replacement therapy remains a cornerstone of treatment in antibody deficiencies and other inborn errors of immunity. While patient preferences between subcutaneous and intravenous immunoglobulin have been studied through questionnaires, no study has yet explored patient perspectives in a free environment. Therefore, we aimed to conduct a sentiment analysis as well as a temporal and geographical analysis on public opinions obtained from social media to better understand patient satisfaction and public perception on immunoglobulin therapy. Methods: A dataset of 43,700 tweets spanning from the 1st of January of 2012 to the 31st of December of 2022 was obtained. A Valence Aware Dictionary for Sentiment Reasoning sentiment analysis was performed, followed by statistical, geographical and temporal analyses. Results: Mean polarity of intravenous immunoglobulin related tweets was 0.1295 (positive), while mean polarity for subcutaneous immunoglobulin was 0.2117 (positive). Temporal analysis through a statistical model demonstrated that the volume of tweets increased over time for both subcutaneous and intravenous treatment. Geographical analysis revealed that the majority of texts originated from the United States. The highest mean polarity was observed in Romania with a mean value of 0.2966, while the lowest polarity was documented in Norway with a mean of -0.0211. Conclusion: Tweets linked to subcutaneous immunoglobulin treatment had a higher average polarity, indicating a more positive public perception. The amount of tweets relating to both therapies showed a tendency to increase as the years progressed, implying an increase in public discussion on immunoglobulin treatment.